Motivasi Filantropi di Kalangan Milenial Muslim Indonesia - Jubba, Hasse; Ishlahuddin, Ishlahuddin; Safitri, Lale Yomi; Huda, Ahmad Fathul (Institut Agama Islam Negeri Kendari, 2023)
Islamic spirituality and the philanthropic spirit of society cannot be viewed as generic and instantaneous. The purpose of this article is to explore the factors that shape the intrinsic motivation of the millennial generation in carrying out philanthropic activities. This article is written using qualitative methods using data obtained from related literature. The data used as analysis material is in the form of secondary data obtained from previous studies, journals, and reports from related institutions such as Charities Aid Foundation and Badan Amil Zakat Nasional RI. The data obtained are analyzed by content analysis methods, at this stage the content under study is interpreted with a focal point on the meaning in accordance with the purpose of the study. The findings of this study show that the high motivation of Muslim millennial philanthropy is driven by the motivation that arises in each of them. Philanthropic activities among Muslim millennials, in addition to being a form of piety, are also a criticism of philanthropic activities so far. The limitation of this study lies in the type of data used, namely secondary data so that it has not been able to describe the state of the millennial generation. Therefore, further analysis using primary data is needed to obtain more accurate results.